Use of a Fission Yeast Platform to Identify and Characterize Small Molecule PDE Inhibitors - Hoffman, Charles S. (Frontiers in Pharmacology, 2022)
Cyclic nucleotide phosphodiesterases (PDEs) have been proven to be targets for which highly selective and potent drugs can be developed. Mammalian genomes possess 21 genes whose products are pharmacologically grouped into 11 families; however related genes from pathogenic organisms display sufficient divergence from the mammalian homologs such that PDE inhibitors to these enzymes could be used to treat parasitic infections without acting on the related human PDEs. We have developed a platform for expressing cloned PDEs in the fission yeast Schizosaccharomyces pombe, allowing for inexpensive, but robust screening for small molecule inhibitors that are cell permeable. Such compounds typically display the expected biological activity when tested in cell culture, including anti-inflammatory properties for PDE4 and PDE7 inhibitors. The genetic pliability of S. pombe also allows for molecular genetic screens to identify mutations in target PDE genes that confer some resistance to these inhibitors as a way of investigating the PDE-inhibitor interaction. This screening method is readily accessible to academic laboratories as it does not require the purification of large quantities of a target protein. This allows for the discovery and profiling of PDE inhibitors to treat inflammation or of inhibitors of targets such as pathogen PDEs for which there may not be a sufficient financial motivation for pharmaceutical companies to identify selective PDE inhibitors using more traditional in vitro enzyme-based screening methods.